An enigmatic case of an uncommon syndrome: the Hughes-Stovin syndrome - Dahi, Firouza; Keese, Michael; Thalhammer, Axel; Schmitz-Rixen, Thomas; Gkremoutis, Asimakis (Annals of vascular surgery, 2019)
Hughes-Stovin syndrome is a disorder characterized by deep vein thrombosis and pulmonary artery aneurysms with potentially life-threatening complications. The case of a 22-year-old Moroccan male patient, presenting with signs of sepsis of unclear etiology, is presented here. Computed tomography (CT) scan revealed thrombosis of the inferior vena cava up to the hepatic veins, thrombosis of both common iliac veins and a thrombus in the right atrium. Primarily suspecting septic thrombosis, surgical thrombectomy was performed. The patient recovered uneventfully and was discharged with oral anticoagulants. Three weeks later, he was admitted again with acute shortness of breath. A new CT scan showed bilateral pulmonary embolism and multiple pulmonary artery aneurysms. Hughes-Stovin syndrome was diagnosed, and high-dose heparin and an immunosuppressant (prednisolon) were administered. Two weeks later, the patient presented again with massive epistaxis and hemoptysis. A CT scan showed diffuse parenchymal bleeding. After prophylactic intubation and conservative treatment, he recovered rapidly and was again discharged uneventfully. Under immunosuppressants, a rapid reduction in the diameter of the pulmonary aneurysms was observed and the patient remained symptom-free during follow-up.
Gesehen am 09.12.2019